The Effect of Short-term, Medium, and Long-term Time Horizons on the Prediction of Future Cash Flows: A Comparative Study of the Ability of Operating Earnings and Cash Flows - Farzaneh Heidarpoor; Mehran Arabi; Mostafa Ghannad (راهبرد مدیریت مالی, 2017)
Cash flow prediction is an essential component of economic decision making, particularly in investment and credit evaluation. This paper examines the comparative predictive ability of earnings and operating cash flows variables on future operating cash flows, during short-term, medium, and long-term periods. For this purpose, the data collected from financial statements of 203 companies listed in Tehran Stock Exchange, during a ten-year period (2005-2015) were used. In regression model, the changes of current operating cash flows (as proxy for future operating cash flows) under the influence of past one, three and five years of earnings and operating cash flows (as predictors), are evaluated. The results from the regression analysis reveal earnings and operating cash flows are significant in predicting future operating cash flows but their predictive powers are different, so that comparative predictive ability of operating earnings variable about future operating cash flows is more than that of the operating cash flow itself. The results also show that using both operating earnings and operating cash flow with each other for the prediction, has better outcomes. Moreover, the results indicate that the longer the period of prediction is, the higher the prediction power will be.